Prospects and Obstacles in the Bilateral Relations between Pakistan and Turkey (Journal of Social Sciences Review, 2023)
Since gaining independence, Pakistan and Turkey have maintained robust diplomatic relations. There are several connections that encompass trade, culture, spirituality, and similar values. The two fraternal nations have already been collaborating to enhance their commercial cooperation with the aim of achieving success in the global market and establishing trade agreements. Pakistan has had strong diplomatic relations with Turkey since its establishment. Both nations hold comparable perspectives on various global and regional matters. There exists a historical, religious, and cultural connection between Pakistan and Turkey. Both nations are situated in highly significant geostrategic regions and hold considerable importance within the Muslim world due to the robustness of their governments, economies, and military capabilities. Despite the mutual positive sentiments between Islamabad and Ankara, their efforts to foster robust economic and trade relations were unsuccessful. This study employs a chronological historical survey and a qualitative research methodology to examine the dynamics and rationales behind the evolution of bilateral interactions throughout history. Additionally, it examines the factors that have hindered the establishment of robust economic links between the two nations, including security concerns and the shared cultural and religious identities. This study will also examine the temporal stability of these factors and explore the potential implications and challenges that may arise from their future interconnections.
Keywords: Pakistan; Turkey; Bilateral Relations; History; Challenges